Review: Agriculture Systems based on IOT - Nayak, Niranjan; kumarSahoo, Bijay; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
The Internet of Things is a collection of interlinked smart devices, physical or virtual appliances, artifacts, animals and entities that have unique identifiers and the capacity to transmit information across a network despite involving human-to-human or human-to-computer communication. Thanks to the integration of various innovations, real-time computing, machine learning, product sensors, and integrated systems, the concept of “Internet of Things” has evolved. Modern areas of embedded systems, mobile sensor networks, and monitoring systems, robotics (such as home and building automation) and so on all relate to the Internet of Things. IOT is capable of influencing the world in which human beings live; specialized industries, networked vehicles and smarter towns are all part of the IOT calculation. Furthermore, the most significant influence could be the application of technology such as IOT to the farming sector. This paper shows the integration of IOT technology with other technologies to enhance agriculture practices and operations.